Benefit-risk tradeoff preferences for chronic hand eczema treatments. (2nd January 2017) - Hauber, A. Brett; Mohamed, Ateesha F.; Gonzalez, Juan Marcos; Otteson Fairchild, Angelyn; Zelt, Susan C.; Graff, Ole
Abstract: Hand eczema affects approximately 16% of the US population. The long-term prognosis is poor, and 5–7% experience severe chronic hand eczema (sCHE) that interferes with daily activities. Treatments for CHE may be ineffective or associated with adverse events (AEs) that may dissuade patients from pursuing or continuing treatment. For quantification of patient experiences and benefit-risk preferences for outcomes associated with CHE treatments, a web-based discrete choice experiment survey was administered to patients in the United States with a self-reported physician diagnosis of CHE and severe symptoms not resolved with topical agents. Respondents answered a series of treatment choice questions, each requiring evaluation of a pair of hypothetical profiles of medications for sCHE defined by efficacy and risk of several AEs. Improvement in CHE clearing of 25–50% was rated from 1.5 to 3.1 times as important as eliminating a 5% risk of permanent bone problems. The mean maximum acceptable risk of permanent vision problems in exchange for an improvement in CHE clearing of 25–50% ranged from 3.4% to 4.8%. This study demonstrated that patients with CHE rated efficacy improvements associated with treatment of sCHE as more important than eliminating the risks of specific AEs.